Impact of Product Design on Purchase Decision of Laptop among College Level Students - Manandhar, Raju Bhai (Tribhuvan University Journal, 2021)
Now-a-days, technology is changing with innovation and development to meet human needs and wants. It assists in communication and shares information with different categories of people and users. It has seen the usage of laptops is increasing these days. Moreover, caused by the quickly storing, shifting, and retrieving the information, consumers can use it to have pertinent information anytime, anywhere. The objective of this study is an impact of product design on purchase decision and to recognize the association between the gender and choice of product design with reference to laptop. The study has been adopted descriptive and causal research design. Primary data are main sources for the survey. The questionnaire survey was applied for collecting primary data. This study targeted the college level students as a sample unit. Two hundred respondents were selected from Kathmandu valley using a convenience sample. Mainly, independent t-test and regression have been adopted to analyze the data. It investigated that purchase decision was positively impacted by product design but gender has no impact on product design for choice of laptop.